Use of Flow Cytometry to Evaluate Phagocytosis of Staphylococcus aureus by Human Neutrophils - Boero, Elena; Brinkman, Iris; Juliet, Thessely; van Yperen, Eline; van Strijp, Jos A. G.; Rooijakkers, Suzan H. M.; van Kessel, Kok P. M. (Frontiers in Immunology, 2021)
Neutrophils play a key role in the human immune response to Staphylococcus aureus infections. These professional phagocytes rapidly migrate to the site of infection to engulf bacteria and destroy them via specialized intracellular killing mechanisms. Here we describe a robust and relatively high-throughput flow cytometry assay to quantify phagocytosis of S. aureus by human neutrophils. We show that effective phagocytic uptake of S. aureus is greatly enhanced by opsonization, i.e. the tagging of microbial surfaces with plasma-derived host proteins like antibodies and complement. Our rapid assay to monitor phagocytosis can be used to study neutrophil deficiencies and bacterial evasion, but also provides a powerful tool to assess the opsonic capacity of antibodies, either in the context of natural immune responses or immune therapies.